Evaluation of Growth and Physiological Responses of Three Rice (Oryza sativa L.) Varieties to Elevated Temperatures - Kurniawan, Dede Yudo; Junaedi, Ahmad; Lubis, Iskandar; Sunarti, Titi Candra (Department of Agronomy and Horticulture, IPB University, 2019)
Temperature is a primary factor that affects the rate of plant development and has great impacts on plant growth, metabolism, and yield. A study was conducted to analyze the effects of elevated temperature on rice morphological and the physiological growth. The research was arranged in a nested randomized block design consisting of two factors, temperatures and rice varieties. Elevated temperatures were provided through the uses of different materials of plastic roof and walls to have an average and maximum temperature of 27.6 °C and 41.6 °C (T1); 28.1°C and 43.8 °C (T2), and 29.5°C and 47.1 C (T3), respectively. The study used three varieties of rice, “Ciasem”, “Ciherang”, and “IR64”. All rice varieties showed signifi cant increases in tiller number per hill and shoot dry weight, but had a decrease in the stomatal conductance, transpiration rate, and SPAD values at grain fi lling stage with the increasing temperatures. The number of tiller per hill increased when temperature was elevated from 27.6 to 28.1 and 29.5°C by about 29.9 and 21.3%, respectively.